2011
DOI: 10.1111/j.1365-2966.2010.17898.x
|View full text |Cite
|
Sign up to set email alerts
|

Orientation effects in quasar spectra: the broad- and narrow-line regions

Abstract: The definitive version can be found at : http://onlinelibrary.wiley.com/ Copyright Wiley-BlackwellWe use the Sloan Digital Sky Survey, along with the NRAO VLA Sky Survey and the Westerbork Northern Sky Survey to define a sample of 746 radio-loud quasars and measure their 330 MHz-1.4 GHz spectral indexes. Following previous authors we take the radio spectral index as an indicator of the orientation towards the quasars such that more pole-on sources tend to have flatter spectral indexes. We use this proxy for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 61 publications
7
54
3
Order By: Relevance
“…[45]). The FWHMs of the lines were always > 2000 km/s [36,102]. The masses of the central black hole are in the range of 10 8−10 M ⊙ (e.g.…”
Section: Pos(nls1)024mentioning
confidence: 99%
“…[45]). The FWHMs of the lines were always > 2000 km/s [36,102]. The masses of the central black hole are in the range of 10 8−10 M ⊙ (e.g.…”
Section: Pos(nls1)024mentioning
confidence: 99%
“…Studies so far have shown that BAL quasars have a wide range of radio spectral indices (α, defined as f ∝ ν α , where f is the radio flux and ν is the frequency), suggesting a full range of orientations (Becker et al 2000). A significant difference between the distribution of α for BAL and non-BAL quasars has not been previously identified, but the sample sizes have typically been small (Fine et al 2011). Montenegro-Montes et al (2008) did identify a difference in the α distributions of their samples-however when they restricted their analysis to include only compact sources the difference disappeared.…”
Section: Introductionmentioning
confidence: 99%
“…This was made possible mostly due to large radio surveys such as FIRST (Becker et al 1995) and NVSS (Condon et al 1998), and allowed the first true studies of the orientation of BAL quasars. Although BAL quasars often do not have extended radio structure which would allow a direct estimate of their orientation, the steepness of radio spectrum can indicate orientation (Fine et al 2011). In general, more edge-on radio sources are dominated by optically thin lobe emission, which has a steep spectrum, and more face-on sources are dominated by relativistically boosted core radio emission, which is optically thick and thus flatter due to synchrotron self absorption.…”
Section: Introductionmentioning
confidence: 99%
“…(1) but for the C iv line. Black-hole mass estimates derived from that line are more controversial because of uncertainties on the geometry of the C iv emitting region, because of the contamination from a putative narrow C iv emission and because virial equilibrium is not expected to hold perfectly for such high ionization lines (Richards et al 2002;Bachev et al 2004;Marziani et al 2006;Fine et al 2011;Assef et al 2011;Wang et al 2011;Richards et al 2011;Marziani & Sulentic 2012). For two systems (H1413+117 and J1131-1231), we also used H β to calculate M BH .…”
Section: Black Hole Mass Measurementmentioning
confidence: 99%